2012
DOI: 10.1002/dvdy.23825
|View full text |Cite
|
Sign up to set email alerts
|

ETV2 expression marks blood and endothelium precursors, including hemogenic endothelium, at the onset of blood development

Abstract: Background: ETV2 has been identified as an important player in embryonic hematopoiesis. However, the cell populations in which this transcription factor is expressed and operates during blood specification remain to be fully characterized. Here we address these issues using ES cells and a transgenic mouse line expressing green fluorescent protein (GFP) under the control of ETV2 regulatory elements, allowing us to observe the tight association between ETV2 expression and the initiation of hematopoiesis. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 66 publications
1
43
1
Order By: Relevance
“…Finally, global transcriptomic analysis revealed the expression of many transcriptional regulators of hematopoietic and/ or endothelial fate including Etv2 in the FLK1 + FOXF1::VENUS + population. Given that the allantois is the main mesodermal tissue where both FOXF1 and ETV2 are expressed at the E7.5 stage of development (Kataoka et al, 2011;Wareing et al, 2012a), these FLK1 + FOXF1::VENUS + ETV2 + cells are most likely localized to this mesoderm derivative which has been shown previously to give rise to hematopoiesis autonomously (Zeigler et al, 2006). Altogether, these findings reveal that in gastrulating embryos a subset of FOXF1-expressing cells can give rise to hematopoietic cells.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Finally, global transcriptomic analysis revealed the expression of many transcriptional regulators of hematopoietic and/ or endothelial fate including Etv2 in the FLK1 + FOXF1::VENUS + population. Given that the allantois is the main mesodermal tissue where both FOXF1 and ETV2 are expressed at the E7.5 stage of development (Kataoka et al, 2011;Wareing et al, 2012a), these FLK1 + FOXF1::VENUS + ETV2 + cells are most likely localized to this mesoderm derivative which has been shown previously to give rise to hematopoiesis autonomously (Zeigler et al, 2006). Altogether, these findings reveal that in gastrulating embryos a subset of FOXF1-expressing cells can give rise to hematopoietic cells.…”
Section: Discussionsupporting
confidence: 58%
“…We and others have previously shown that the ETS transcription factor ETV2 is expressed in mesodermal progenitors which give rise to both hematopoietic and vascular system, and that Etv2 −/− embryos lack both lineages (Kataoka et al, 2011;Lee et al, 2008;Wareing et al, 2012b). Whilst FLK1 + cells are still detected at the expected frequency in Etv2 −/− embryos, the TIE2 + population is drastically reduced (Wareing et al, 2012a); we therefore analyzed the co-expression of FOXF1::VENUS and TIE2 in wild-type, heterozygous or homozygous null Etv2 embryos (Fig. 4D).…”
Section: Foxf1 Expression Is Initiated Within the Early Flk1 + Mesodementioning
confidence: 79%
“…It is interesting that the expression of mouse Etv2 was transiently detected in the beginning of hematopoiesis and was barely detectable in hematopoietic tissues at later stages, such as the aortagonad-mesonephros and fetal liver in embryos and in the bone marrow and spleen in adults (54)(55)(56). A dramatic down-regulation of Etv2 during hematopoietic differentiation is also observed in zebrafish (35) and Xenopus (57).…”
Section: Discussionmentioning
confidence: 99%
“…Etv2 + Flk1 + mesodermal cells give rise to both endothelial cells and blood (Kataoka et al, 2011, Wareing et al, 2012). Whether the Etv2 + Flk1 + mesodermal progenitor gives rise to a non-hemogenic endothelial cell or a HE cell was recently reported to be controlled, at least in part, by Runx1 (Eliades et al, 2016).…”
Section: Regulation Of Runx1 Expression During the Specification Of Hmentioning
confidence: 99%